2013
DOI: 10.1055/s-0033-1335048
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Anatomy - Evaluation of Integrative Education in Radiology

Abstract: !Purpose: Evaluation and analysis of the integrative course "Radiological Anatomy" established since 2007 at the Medical School Hannover (MHH) in comparison with conventional education. Materials and Methods: Anatomy and radiology are usually taught separately with a considerable time lag. Interdisciplinary teaching of these associated subjects seems logical for several reasons. Therefore, the integrative course "Radiological Anatomy" was established in the second year of medical education, combining these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Small group tutorials are an interactive form of teaching with many studies reporting a strong student preference for teaching with interactive case based discussions 13 . Malek et al reported improved enjoyment and concentration with significantly better learning outcomes when using cased based teaching in Radiology 14 . It is clear that educational strategies such as small group teaching, which actively engages students, helps to enhance motivation and foster critical thinking skills 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Small group tutorials are an interactive form of teaching with many studies reporting a strong student preference for teaching with interactive case based discussions 13 . Malek et al reported improved enjoyment and concentration with significantly better learning outcomes when using cased based teaching in Radiology 14 . It is clear that educational strategies such as small group teaching, which actively engages students, helps to enhance motivation and foster critical thinking skills 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified factors supporting radiology. An evaluation of the curriculum demonstrated the positive effect of early implementation of radiology in the coursework [4,5]. Likewise, practical training using case studies [6,7] and integrative instruction involving other subjects [5,8] particularly increase students' motivation, thus enhancing the image of radiology among students.…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of the curriculum demonstrated the positive effect of early implementation of radiology in the coursework [4,5]. Likewise, practical training using case studies [6,7] and integrative instruction involving other subjects [5,8] particularly increase students' motivation, thus enhancing the image of radiology among students. Due to close personal contact and hands-on activity, a practicum in radiology such as a medical clerkship particularly offers an opportunity to encourage students in a subject area [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The utility and efficacy of imaging techniques in delivering anatomy knowledge can be demonstrated to students during this early exposure to radiology (Schober et al, ), thus enhancing their motivation to learn. This can improve their comprehension of important anatomic and radiologic details (Dettmer et al, ) and provide a deeper understanding of the basic sciences (Bhogal et al, ). It can also support their learning of human morphology and physiology (Pascual et al, ) and greatly facilitate their ability to interpret computed tomography (CT) images during the clinical years (de Barros et al, ).…”
Section: Introductionmentioning
confidence: 99%